Cellulose Ether-Based Liquid Crystal Materials: Review Article - Basta, Altaf H.; Lotfy, Vivian F.; Micky, Jehane A.; Salem, Aya M. (Journal of Research Updates in Polymer Science, 2021)
The development of liquid crystal materials via nanotechnology has become an interesting subject of research in optical material chemistry. One of the significant nanomaterials is cellulose-based nanoparticles. In this review article, we highlighted the classification of liquid crystal materials (LCs), and types of cellulose-NPs and their characterization as LCs materials. Finally, we present our promising data on the synergistic effect of cellulose-NPs on liquid crystal behavior of ethyl cellulose- and hydroxypropyl cellulose- nanocomposites.